Components of Body–Self Ambiguity in Dermatology Patients: A Qualitative Study - Abdi, Mansour; Bagheri, Parisa; Ranjbar, Maryam (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to explore the lived experiences and psychological components of body–self ambiguity among patients with chronic dermatological conditions, focusing on how individuals interpret, negotiate, and reconstruct the meaning of their altered embodiment. This qualitative phenomenological study was conducted with 16 dermatology patients (9 women and 7 men) from clinical centers in Tehran between March and August 2025. Participants were selected through purposive sampling to ensure variation in age, gender, diagnosis, and illness duration. Data were collected using semi-structured, in-depth interviews that invited participants to describe their personal experiences of body–self disconnection and social perception. Interviews were recorded, transcribed verbatim, and analyzed through Braun and Clarke’s six-phase thematic analysis using NVivo 14 software. Theoretical saturation was achieved after the sixteenth interview. Trustworthiness was ensured through triangulation, member checking, and maintaining an audit trail of analytical decisions. Analysis revealed four overarching themes representing the components of body–self ambiguity in dermatology patients: (1) Fragmented Body Awareness, describing disconnection from one’s bodily image and sensory estrangement; (2) Emotional Turbulence in the Self–Body Relationship, involving shame, anxiety, and emotional fatigue in response to visible changes; (3) Social Mirror and External Reflection, capturing stigma, social withdrawal, and the internalization of others’ judgments; and (4) Meaning Reconstruction and Adaptation, denoting acceptance, spirituality, and creative self-expression as pathways toward re-integrating body and self. These findings highlight body–self ambiguity as a fluid and multidimensional experience shaped by emotional, social, and cultural contexts. The study concludes that dermatological illness profoundly alters patients’ bodily self-concept, evoking fragmentation yet also fostering potential for meaning reconstruction.